The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/aogs.12559
|View full text |Cite
|
Sign up to set email alerts
|

Decreased umbilical orexin‐A level is associated with idiopathic polyhydramnios

Abstract: Idiopathic polyhydramnios was associated with decreased umbilical serum orexin-A levels. Our results provide evidence that orexin-A expression may be involved in amniotic fluid regulation, causing polyhydramnios by downregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Maternal serum orexin‐A level is higher than the umbilical cord orexin‐A level. Inconsistent with our results, Cho et al, 34 and Yilmaz et al 35 showed a positive and significant correlation between maternal and umbilical cord serum orexin‐A levels. Orexin‐A is produced during pregnancy from the hypothalamus (blood–brain barrier transport) 7 and placenta 2 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Maternal serum orexin‐A level is higher than the umbilical cord orexin‐A level. Inconsistent with our results, Cho et al, 34 and Yilmaz et al 35 showed a positive and significant correlation between maternal and umbilical cord serum orexin‐A levels. Orexin‐A is produced during pregnancy from the hypothalamus (blood–brain barrier transport) 7 and placenta 2 .…”
Section: Discussionsupporting
confidence: 83%
“…Consistent findings are found in Aran et al 38 study who observed that orexin‐A level in CSF does not significantly correlate with the infant birth weight. In contrast, Cho et al 34 reported that maternal/cord serum orexin‐A levels have a negative association with birth weight. Moreover, Kahraman et al 39 showed that serum orexin‐A level found in malnourished children was not related to their height, although there was a negative relationship between serum orexin‐A levels with BMI and children's weight.…”
Section: Discussionmentioning
confidence: 89%